2008
DOI: 10.1111/j.1742-4658.2008.06634.x
|View full text |Cite
|
Sign up to set email alerts
|

Location of the Bombyx mori 175 kDa cadherin‐like protein‐binding site on Bacillus thuringiensis Cry1Aa toxin

Abstract: To identify and gain a better understanding of the cadherin‐like receptor‐binding site on Bacillus thuringiensis Cry toxins, it is advantageous to use Cry1Aa toxin, because its 3D structure is known. Therefore, Cry1Aa toxin was used to examine the locations of cadherin‐like protein‐binding sites. Initial experiments examining the binding compatibility for Cry1Aa toxin of partial fragments of recombinant proteins of a 175 kDa cadherin‐like protein from Bombyx mori (BtR175) and another putative receptor for Cry1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 54 publications
1
28
0
1
Order By: Relevance
“…Regarding the interaction of Cry1Ab monomer with Bt-R 1 receptor, previous work showed that domain II, loop ␣-8, loop 2, and loop 3 are involved in the binding of Cry1Ab toxin to this receptor (2,16,32 (17,18). Monomeric structures of the three loop 3 mutants characterized here were only affected in the binding with the CR12 fragment of Bt-R 1 and not with a Bt-R 1 fragment corresponding to CR7-CR12 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the interaction of Cry1Ab monomer with Bt-R 1 receptor, previous work showed that domain II, loop ␣-8, loop 2, and loop 3 are involved in the binding of Cry1Ab toxin to this receptor (2,16,32 (17,18). Monomeric structures of the three loop 3 mutants characterized here were only affected in the binding with the CR12 fragment of Bt-R 1 and not with a Bt-R 1 fragment corresponding to CR7-CR12 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Insect cadherins are composed of an ectodomain formed by 11 or 12 cadherin repeats (CRs), a transmembrane domain, and an intracellular domain (14). The exposed loops of Cry1A domain II have been directly involved in binding with cadherin in M. sexta, H. virescens, and B. mori (15)(16)(17)(18). Three Cry1Ab binding sites were mapped in CR7, CR11, and CR12 of the M. sexta Bt-R 1 (15,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, residue Tyr445 in loop 3 of Cry1Aa domain II was identified as being important in binding to the cadherin BtR175 of Bombyx mori (Atsumi et al, 2005) while Val582 in domain III was shown to be important for interaction with aminopeptidase N (Atsumi et al, 2008). In parallel, there have been studies to map regions of receptors that may interact with the toxins (Pigott and Ellar, 2007) but even when a common class of receptor (eg a cadherin) is considered, there is little correspondence between regions interacting with different toxins.…”
mentioning
confidence: 99%
“…It has been proposed that a series of different binding events participate in Cry toxin action, such as the primary binding interaction of activated Cry1A toxin with aminopeptidase N (APN) or alkaline phosphatase (ALP) by domain II loop 3 and ␤-16 of domain III (13)(14)(15). Binding to cadherin-like protein (CAD) follows by means of domain II-exposed loops ␣-8, 2, and 3, promoting cleavage of helix ␣-1 of domain I and inducing toxin oligomerization (14)(15)(16)(17)(18)(19). Finally, it was reported that binding of the oligomeric Cry1A toxin to ALP and APN receptors by means of domain II loop 2 is involved in toxin insertion into membrane and cell lysis (2,15,20).…”
mentioning
confidence: 99%